Busulfan‐based myeloablative conditioning regimens for haploidentical transplantation in high‐risk acute leukemias and myelodysplastic syndromes. (3rd August 2018) - Gayoso, Jorge; Balsalobre, Pascual; Kwon, Mi; Herrera, Pilar; Bermúdez, Arancha; Sampol, Antonia; Jiménez, Santiago; López‐Corral, Lucía; Serrano, David; Piñana, Jose Luis; Pascual, María J.; Heras, Inmaculada; et al.
Abstract: Background: High‐risk acute leukemia (AL) and myelodysplastic syndrome (MDS) remain a therapeutic challenge. Unmanipulated haploidentical‐related donor transplantation based on a myeloablative conditioning regimen (HAPLO‐MAC) and post‐transplant cyclophosphamide (PT‐Cy) as prophylaxis against graft vs host disease (GvHD) is now a promising rescue strategy that could become universally available. Objective: To evaluate the results of HAPLO‐MAC with PT‐Cy in patients with AL and MDS reported to the Haploidentical Transplantation Subcommittee of the Spanish Group for Hematopoietic Transplantation (GETH). Patients and methods: We report our multicenter experience using an IV busulfan‐based HAPLO‐MAC regimen and PT‐Cy for treatment of 65 adults with high‐risk AL and MDS. Results: Engraftment was recorded in 64 patients (98.5%), with a median time to neutrophil and platelet recovery of 16 and 27 days, respectively. The cumulative incidence of grade II‐IV acute GvHD and chronic GvHD was 28.6% and 27.5%, respectively. After a median follow‐up of 31 months for survivors, the cumulative incidence of non‐relapse mortality and relapse at 2 years was 18.8% and 25%, respectively. Estimated 30‐month event‐free survival and overall survival were 56% and 54.5%, respectively. Conclusion: HAPLO‐MAC comprising an IV busulfan‐based conditioning regimen enabled long‐term disease control with acceptable toxicity in high‐risk AL and MDS.